Atmospheric surface layer spectra over a tropical desert station during Indian summer monsoon - PATIL, M. N.; PARASNIS, S. S. (MAUSAM, 2003)
Characteristics of turbulence have been studied using the observations of wind components (u, v and w) and temperature (T) collected by fast response sensor the sonic anemometer (8.33 Hz) during the Monsoon Trough Boundary Layer Experiment in 1990. The analysis showed that the spectra of wind and temperature obeyed the Monin-Obukhov scaling. The spectral curve showed a slope of –2/3 in high frequency portion which indicated the existence of inertial subrange. The diurnal variation in the eddy sizes were brought out.